OCULAR CHANGES IN PATIENTS ON LONG TREATMENT WITH HYDROXYCHLOROQUINE - Singh, Anuradha; Patyal, Sagarika; Vasudev, Vivek; Sharma, Vijay; Trehan, Hemant Singh (Indonesian Vitreoretinal Society, 2021)
Introduction: To study the ocular changes in patients on long term treatment with Hydroxychloroquine (HCQ); and detect means for early detection of toxicity.Methods: We conducted a cross-sectional observational study at a tertiary care hospital, in which 100 patients, male and female, aged 35 years or more, taking HCQ for 5 years or more were included. Patients with any known ocular or systemic diseases were not included. Indication, dosage, duration and cumulative dose of HCQ intake were recorded. History of ocular symptoms, visual acuity, colour vision, complete ophthalmic examination, visual field using Amsler grid and 10-2 Humphrey’s automated fields (HVF), Spectral Domain Optical Coherence Tomography (SD-OCT), colour fundus photography, fundus fluorescein angiography (FFA) and fundus autofluorescence (FAF) were recorded. The data was analyzed using descriptive and inferential analysis.Result: 15% of the study population showed signs of HCQ related ocular toxicity. 17%, 21% and 10% patients had abnormal SD-OCT, HVF and FAF findings respectively.Conclusion: HCQ related ocular toxicity has been found in patients in the absence of symptoms. Objective tests like HVF, SD- OCT and FAF were more useful in early detection of toxicity than subjective tests such as Amsler grid, colour vision and FFA.